1985
DOI: 10.1029/ja090ia07p06475
|View full text |Cite
|
Sign up to set email alerts
|

Quiet ionospheric currents of the northern hemisphere derived from geomagnetic field records

Abstract: A special selection of extremely quiet 1965 geomagnetic daily variation records from North America, Europe, central Asia, and east Asia was used to determine monthly spherical harmonic analysis coefficients representing the Sq fields from these regions. The coefficients permitted a separation of the external and internal contributions to the daily variations. Month‐by‐month behavior of the equivalent external current system and contours of the daily range of this current showed regional differences in amplitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 15 publications
6
35
0
Order By: Relevance
“…The difference between the values of the northern and southern foci indicates the total current intensity, which is about 300 kA, for the summer season. This is very high, when compared with the summer current intensities of other global regions (Malin and Gupta, 1977;Campbell and Schiffmacher, 1985). As observed in this study, Malin and Gupta (1977) also have reported a maximum intensity of current for Sq when its focus is located at mid-Pacific.…”
Section: Equivalent Ionospheric Source Current Systemssupporting
confidence: 62%
See 2 more Smart Citations
“…The difference between the values of the northern and southern foci indicates the total current intensity, which is about 300 kA, for the summer season. This is very high, when compared with the summer current intensities of other global regions (Malin and Gupta, 1977;Campbell and Schiffmacher, 1985). As observed in this study, Malin and Gupta (1977) also have reported a maximum intensity of current for Sq when its focus is located at mid-Pacific.…”
Section: Equivalent Ionospheric Source Current Systemssupporting
confidence: 62%
“…Compared with the position of Sq foci in the North American and European regions, the Sq focus in the northern hemisphere in the East Asian sector is situated at a relatively lower latitude (Campbell and Schiffmacher, 1985). The mid-latitude pre-noon focus vortex of current, though not clearly seen in winter (Fig.…”
Section: Westward Lag Of Sq Focusmentioning
confidence: 99%
See 1 more Smart Citation
“…5b are those for the intermediate latitude. The HA daily variation at this intermediate latitude was obtained in a manner similar to that used by Campbell and Schi macher (1985). They stated that it is a reasonable expectation that in quiet times the average surface ®eld signatures of ionospheric source currents should change smoothly with latitude.…”
Section: Resultsmentioning
confidence: 99%
“…The position of Sq currents was affected by the position of the geographic and geomagnetic poles with respect to these regions (Campbell and Schiffmacher, 1985). In the African sector of the Northern Hemisphere at Tamanrasset and M'bour (row 11, columns 2, 3), the Y morning maximum, in winter, is very small or disappears: this was previously observed on magnetic data by Van Sabben (1964), Mayaud (1965b) and also on incoherent scatter sounder data by Mazaudier and Venkateswaran (1985).…”
Section: Discussionmentioning
confidence: 99%